Parasite prevalence in fecal samples from shelter dogs and cats across the Canadian provinces - Villeneuve, Alain (Parasit Vectors, 2015)
BACKGROUND: In Canada, surveys of enteric parasites in dogs and cats have been reported sporadically over the past 40 years, mostly focusing on a specific region. The present work was performed to determine the current prevalence of various parasites in fecal samples from shelter dogs and cats across the Canadian provinces. METHODS: A total of 1086 dog and 636 cat fecal samples from 26 shelters were analysed using a sugar solution double centrifugal flotation technique. Prevalences (national, regional, provincial, age and parasite-specific), were calculated and compared using the Fisher-Exact test. A multiplex PCR was performed to distinguish Taenia spp, Echinococcus granulosus and E. multilocularis on samples positive for taeniid eggs. RESULTS: Overall, 33.9% of dogs and 31.8% of cats were positive for at least one parasite. Toxocara canis and T. cati were the most prevalent parasite present in fecal samples followed by Cystoisospora spp. Prevalence in dogs was similar across the Atlantic, East, West and Pacific regions, while prevalence in cats varied regionally. Eggs of E. granulosus/E. canadensis were detected in samples from dogs from BC, AB, and ON. CONCLUSIONS: Data from this study will help in the development of strategies, based on the level of risk per geographic location for the prevention and response to these parasites in pets and free-roaming and shelter animals in Canada.